Aqueous hibiscus extract as a potential natural pH indicator incorporated in natural polymeric films. (March 2019) - Peralta, Juliana; Bitencourt-Cervi, Camila M.; Maciel, Vinicius B.V.; Yoshida, Cristiana M.P.; Carvalho, Rosemary A.
Highlights: Films containing aqueous hibiscus extract were developed as a natural pH indicator. Natural polymers (chitosan, gelatine and starch) were used for the film production. Great colour change from pink (pH = 2.0) to yellow (pH = 13.0) were observed. The pH indicator associated with intelligent packaging shows the quality products. Abstract: Intelligent packaging system was developed based on natural polymeric films (chitosan, gelatin and starch), containing bioactive compounds from aqueous hibiscus extract (HAE). Anthocyanin, a compound present on HAE, changes colour under different pH conditions. Thus, the application of HAE as a natural pH indicator with visible colour variation incorporated into renewable materials to allow for simple, economic, and easy disposal, can be considered an invocation in the area of intelligent packaging system. Films containing HAE (25 g/100 g of filmogenic dispersion, intelligent films) were produced by casting using 2 g of starch, gelatin or chitosan/100 g of filmogenic dispersion and 30 g of sorbitol/100 g of macromolecules. These films were characterized by the colour change at different pH values (from 2.2 to 8.0 and 13.0), water content, total soluble matter, light barrier properties and morphological structure. Intelligent films presented homogeneous surfaces without visible defects. The colour variation of intelligent films was visibly observed and completely dependent on pH. This was associated with the presence of anthocyanins and other phenolic compounds in HAE. The addition of HAE in the films provoked a significant increase in the water content. A significant increase was observed only for the starch film for total soluble matter. The gelatin films presented a barrier to light. The proposed device could be used as an alternative natural pH indicator in intelligent packaging systems.